IMPLEMENTATION OF ECO-INNOVATION IN ENTERPRISES - Koszarek-Cyra, Aleksandra (Acta Universitatis Nicolai Copernici. Zarządzanie, 2020)
Implementing eco-innovation in the face of critical environmental degradation has become a necessity. It is necessary to create procedures that companies could apply when they implementing green initiatives. This article presents a proposal for an eco-innovation implementation procedure that highlights the importance of the planning stage. The scheme was developed on the basis of a critical review of the literature and conclusions of the research that was carried out as part of the doctoral dissertation ‘Environmental management in SME enterprises of the śląskie voivodship’.